1990
DOI: 10.1080/10862969009547695
|View full text |Cite
|
Sign up to set email alerts
|

Student Factors Related to Variability in Learning Word Meanings from Context

Abstract: This study examined how vocabulary knowledge, the familiarity of concepts, and analytic reasoning affect sixth-grade students' ability to learn word meanings from the context of natural passages in a basal reading textbook. The results indicated that students with higher levels of general vocabulary knowledge learned relatively more, even though they had less room for improvement. Low students were at a disadvantage not only because they initially knew fewer words but also because they understood words less we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
0
6

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(67 citation statements)
references
References 21 publications
2
59
0
6
Order By: Relevance
“…On the other hand, those same readers are less likely to encounter ceiling effects because any given text is more likely to include words that are novel to them. This argument made by Shefelbine (1990), however, concerns the effect of initial vocabulary skill on vocabulary growth. This is in contrast to the current study, which addresses the relationship of reading skill and vocabulary growth.…”
Section: Study Questionsmentioning
confidence: 95%
See 1 more Smart Citation
“…On the other hand, those same readers are less likely to encounter ceiling effects because any given text is more likely to include words that are novel to them. This argument made by Shefelbine (1990), however, concerns the effect of initial vocabulary skill on vocabulary growth. This is in contrast to the current study, which addresses the relationship of reading skill and vocabulary growth.…”
Section: Study Questionsmentioning
confidence: 95%
“…There was no hypothesis for the second question in this study because no previous research has addressed this specific question and there might be some reason to expect either a two-sided or a one-sided Mathew effect. As Shefelbine (1990) pointed out, readers with lower initial vocabulary knowledge will necessarily have an impoverished semantic context for inferring new word meaning, which might lead to lower rates of vocabulary growth. On the other hand, those same readers are less likely to encounter ceiling effects because any given text is more likely to include words that are novel to them.…”
Section: Study Questionsmentioning
confidence: 99%
“…Therefore, the ability to understand individual words plays an important role in semantic learning (cf. Cain et al, 2004;Ewers & Brownson, 1999;Sénéchal et al, 1995;Shefelbine, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Equally though, existing vocabulary knowledge is a significant predictor of semantic learning following reading (e.g., Cain et al, 2004;Ewers & Brownson, 1999;Sénéchal, Thomas, & Monker, 1995;Shefelbine, 1990). Cain et al (2004) found that the ability to infer word meanings from context was predicted by both oral vocabulary and reading comprehension but that reading comprehension emerged as the stronger predictor.…”
mentioning
confidence: 99%
“…The descriptive data also indicated that the participants with the lowest scores on the pre-test made the greatest gains. However, because participants with higher pretest scores could learn fewer words than those with lower pre-test scores, it is necessary to examine relative learning gains rather than actual learning gains in this analysis (Shefelbine 1990;Horst, Cobb, & Meara 1998). However, the absence of inferential analysis and effect sizes in all of the comparisons between the groups makes it difficult to clearly determine the validity of these conclusions.…”
Section: Background To the Studymentioning
confidence: 99%